Uncovering Student Thinking About Mathematics in the Common Core, Grades K-2 : 20 Formative Assessment Probes. - Tobey, Cheryl Rose (SAGE Publications, 2013)
Get to the core of your students' understanding of math!Quickly and reliably identify your primary students' math knowledge with these convenient and easy-to-implement diagnostic tools! Tobey and Fagan provide 25 new assessments specifically for Grades K-2 and directly aligned with the Common Core. Organized by strand, the probes will enable you to: Quickly and objectively evaluate each child's prior knowledge of basic math and numeracy Systematically address common mistakes and obstacles before they become long-term problems Make sound instructional choices to improve all student.